2007
DOI: 10.1038/sj.jhh.1002250
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac repolarization and its relation to ventricular geometry and rate in reverse remodelling during antihypertensive therapy with irbesartan or atenolol: results from the SILVHIA study

Abstract: Hypertensive left ventricular (LV) hypertrophy is associated with a substantial risk for malignant arrhythmias and sudden death. According to recent results, antihypertensive therapy with the angiotensin II type 1 receptor blocker irbesartan reverses both structural and electrical remodelling. However, the relation between the LV geometric pattern (concentric vs eccentric) and electrical reverse remodelling has not been characterized, neither has the relation between repolarization and rate (QT/RR and JT/RR re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
(79 reference statements)
1
5
0
Order By: Relevance
“…These drugs reduce the QT interval. [30][31][32]69,70 Experimental studies have also demonstrated that ACEis reduce the QT interval. 1,3,48,74 The effects of either an ACEi or an ARB on the QT interval are exerted via mechanisms that regulate also the QT interval.…”
Section: Ace Inhibitors and Arbsmentioning
confidence: 95%
“…These drugs reduce the QT interval. [30][31][32]69,70 Experimental studies have also demonstrated that ACEis reduce the QT interval. 1,3,48,74 The effects of either an ACEi or an ARB on the QT interval are exerted via mechanisms that regulate also the QT interval.…”
Section: Ace Inhibitors and Arbsmentioning
confidence: 95%
“…In hypertension associated with obesity, the duration of QTc interval is prolonged and tended to be decreased after blood pressure control and weight loss 6 . Antihypertensive drugs (angiotensin converting enzyme inhibitors and angiotensin receptor blockers) reduced the duration of QT interval due to their effects on the left ventricular mass which increases in hypertension 7, 8, 9. Beta-adrenoceptor blockers may also reduce the duration of the QT interval in a dose-dependent manner without having any effect on the blood pressure10, 11 while calcium channel blockers (dihydropyridine) do not exert a beneficial effect on QT interval 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, its reduction is thought to be associated with regression of cardiac hypertrophy in terms of the reduction of left ventricular mass. Indeed, it was shown that antihypertensive drugs reduce QT duration as well as cardiac mass in hypertensive subjects which in turn reduces the incidence and severity of ventricular arrhythmias and the risk for cardiovascular events . Still, the relationship between QT reduction, antihypertensive and antihypertrophic action of antihypertensives is not understood.…”
mentioning
confidence: 99%
“…However, an inconsistency is seen in the clinic as a different influence of antihypertensives on QT duration was described after the reduction of BP and cardiac mass in the hypertensive population. Moreover, marked differences in reduction of QT abnormalities were published in spite of similar or even equivalent BP‐reducing action . From the entire group of antihypertensive drugs, dihydropyridine calcium channel blockers (CCBs) mediate their antihypertensive effects via vasodilatation but their efficacy could be significantly decreased by counter‐regulatory cardiac and the renal activation by the baroreflex that may influence cardiac repolarization .…”
mentioning
confidence: 99%